Die Transzendenz der Gewalt im Angesicht der Wende – Thomas Hettches Nox und die besondere Konstellation der Postmoderne - Szałagiewicz, Marek (Studia Germanica Posnaniensia, 2013)
The year 1989 not only marks the end of the Cold War and the German reunification, it also initiates a specific period in which post-modern philosophy reached its peak. The political and social situation in the Occident seemed to be so stable that scientists as well as the general public started to speak of the “end of history”. This was accompanied by a certain feeling of loss of reality, intensified by the development of electronic media. This little Belle Époque of the 90s was the breeding ground for a peculiar understanding of violence that was expressed in popular culture or even in such phenomena as extreme sports. The violence was in fact seen as one of the few ways to transcend the boundaries of the world not only broadcasted but also created by the mass media. With the spirit of the times corresponds the novel Nox by Thomas Hettche. The text, considered as one of the first novels of German Reunification, brings up and connects two transitions – the one, regional, from the divided to the reunified Germany and the other, related to all spheres of reality, from modernity to post-modernity. In both processes, the infamous, autotelic violence emerges (Reemtsma), this time, in the constellation of postmodernity, under the guise of transcendence.